Struktur Logika Dalam Teologi Islam: Telaah Kritis Terhadap “The Logical Structure Of Islamic Theology” Karya Josef Van Ess - Mohammad Nasrul Amin (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2017)
Van Ess’s research tries to uncover the logical structure of Islamic Theology. His research is the intellectual – respond from Al Baghdadhi’s statement that nobody among the older fuqaha had shown any interest in logic except Al Mawardi. He took systematic and historic approach in order to analyze, describe and elaborate the logical structure of Islamic Theology. In addition, researcher tries to discover three points here, 1) The logical structure of Mutakalimun, 2) The academic contribution from Van Ess’s Thought and 3) The Critique on Van Ess’s Research. In the result, logical structure of Islamic Theology is broadly influenced by Aristoteles’ syllogism, as well as Stoic. Besides that, there is misconception about the existence of logic among Mutakalimun, they didn’t placed logic as the appropriate place and it impacted on the sense of kalam itself; conflict and apologetic. However, it could be solved through Syafi’i’s theory on Qiyas and Fazlurrahman’s theory on double movement. But how far the influence and solution could be traced, according to this writing, it needs a next deeper study.